Green Transformation and its Application on Shipping Service Complex - Wang, Xuefeng; Wang, Mingyang; Wu, Pengcheng; Huang, Tianrong; Jiang, Huixian (International Journal of Natural Sciences Research, 2019)
This article is written under the context of old construction Shanghai Shipping Service Complex (SSC) around the port. These buildings are too old to keep pace with the development and urgent to be upgraded. This article generally introduced the green transformation methods and application on the existing buildings in the urban old port district. In order to facilitate the green transformation of the SSC, we carried out an investigation upon the construction, structure design, specific building materials and interior decoration of the original building to form a general understanding. By combining its location features and functional orientation, the optimal transformation scheme was completed through the comparison of the building projects, structural analysis, and energy-saving transformation program. Meanwhile, the effect of the preliminary scheme was tested via energy-saving calculation, computer simulation and field testing. A third party was introduced to certificate the technological application to prove the safety and reliability of the scheme.